Dynamics of nutrients, plankton and benthic macroinvertebrates in rohu Labeo rohita ponds with various densities of common carp Cyprinus carpio - Rahman, Mohammad Mustafizur; Jo, Qtae; Verdegem, Marc C.J.; Wahab, Md Abdul; Hossain, M. Y.; Lee, Ji Hyun; Gong, Yeong (2008)
Common carp (Cyprinus carpio) is specialized to feed on benthic organisms and in doing so affects nutrient availability, which enhances photosynthesis. Therefore, it is commonly used in polyculture pond to increase natural food for planktivorous fish. However, high density of common carp increases soluble P precipitation and water turbidity, which reduce photosynthesis and the related natural food production. Considering both positive and negative effects, stocking density of common carp is important. In this study, we monitored the N, P, phytoplankton, zooplankton and benthic macroinvertebrates dynamics and fish yield in rohu (Labeo rohita) (density: 1.5 m-2) ponds with various densities of common carp (0, 0.5 and 1 m-2; further referred as 0C, 0.5C and 1C, respectively) under fed and unfed conditions. The ultimate objective was to optimize a fish combination and density for South Asian carp polyculture farmers.